Implementasi Sistem Pembayaran Digital Sebagai Strategi Mitigasi Risiko Transaksi pada Reseller Fashion Multi-Channel - Kurniawati Kurniawati; Ahdiyat Agus Susila; Moh. Abd. Rahman (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the implementation of digital payment systems as a transaction risk mitigation strategy for fashion reseller businesses employing multi-channel sales models. The rising prevalence of digital fraud and transfer proof manipulation among micro-enterprises in Probolinggo Regency highlights the urgent need for systematic risk governance using ERM COSO, TAM, and Risk-Return Trade-Off frameworks. This research employs a qualitative approach with a multiple-case study design, utilizing replication logic to construct robust theoretical explanations. Data were collected through in-depth interviews, observations, and documentation from ten informants, and subsequently analyzed using a cross-case matrix. The novelty of this study lies in the finding that past experiences with financial losses act as the primary determinant, shifting the focus of technology adoption from perceived ease of use to asset security, alongside the identification of the operator's role in closing the reconciliation gap between digital systems and field practices. The findings indicate that 90% of the informants (9 out of 10 informants) rationally chose to bear the Merchant Discount Rate (MDR) costs for transaction security, and 100% of the informants consistently implemented daily reconciliation as their primary risk mitigation practice. While digital payment systems effectively mitigate conventional cash payment risks, they demand more complex managerial capacities to address emerging challenges such as payment settlement delays. This study contributes to the development of an adaptive risk management model that integrates the principles of hifdz al-mal and maslahah into operational policies. Theoretically, this research enriches the literature on SME risk management through the integration of cross-frameworks, while practically, the findings provide a strategic guide for policymakers in designing digitalization interventions based on risk segmentation and the digital literacy levels of business owners.